2002
DOI: 10.2176/nmc.42.224
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Regrowth of Solitary Subependymal Giant Cell Astrocytoma. Case Report.

Abstract: A 48-year-old female presented with a subependymal giant cell astrocytoma (SEGA) without tuberous sclerosis manifesting as memory and mental disturbance. Magnetic resonance imaging showed a huge mass which was well-demarcated and extended from the anterior horn of the right lateral ventricle to the septal area on the right side. Surgery was performed with partial removal of the tumor. The histological diagnosis was typical SEGA. One year postoperatively, follow-up magnetic resonance imaging revealed marked reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…7,10,15,17,20,21 It is important to note that none of the previously reported cases were subjected to TSC1/2 gene sequencing, leaving the histogenesis of these particular lesions unclear. Nevertheless, the absence of clinical features of TSC in patients with solitary SEGA has been attributed to somatic mosaicism.…”
Section: 21 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,15,17,20,21 It is important to note that none of the previously reported cases were subjected to TSC1/2 gene sequencing, leaving the histogenesis of these particular lesions unclear. Nevertheless, the absence of clinical features of TSC in patients with solitary SEGA has been attributed to somatic mosaicism.…”
Section: 21 Discussionmentioning
confidence: 99%
“…Approximately 38 cases of SEGA in the absence of clinical features of TSC have been described, 7,10,11,15,[17][18][19]21 with the first case reported by Halmagyi and colleagues in 1979. 7 Bonnin et al reported on 22 cases of SEGA, and only 5 patients among these cases carried a clinical diagnosis of TSC.…”
Section: 21 Discussionmentioning
confidence: 99%
“…A recent study revealed biallelic mutation of TSC1 or TSC2 , leading to mTOR pathway activation in 5/6 SEGAs tested in patients with TSC 21 . Histologically confirmed SEGA alone had historically been considered as sufficient for the definite diagnosis of TSC, 22 and several reported cases of isolated SEGA without any other clinical manifestations were considered to be “forme fruste” of TSC with somatic mosaicism 9–14 . However, most of those cases were reported without molecular analysis for TSC gene mutations or somatic mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of SEGA in TSC ranges from 5.8% to 18.5%, 2–7 while radiologically detected subependymal nodules (SENs), which are believed to be the precursor of SEGA, are seen in more than 90% of patients with TSC 5–8 . Although it is controversial whether SEGA occurs outside the setting of TSC, a significant number of cases in which patients with solitary SEGA had no other stigmata of TSC, have been reported 9–14 . According to the revised diagnostic criteria of TSC, 15 these cases are best classified as “possible TSC”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation